INTEGRASI CERITA RAKYAT LEGENDA DANAU TOBA DALAM PEMBELAJARAN BAHASA INDONESIA SEBAGAI PENGUATAN IDENTITAS BUDAYA - Tesalonika Tampubolon; Maharani br Tarigan; Mutiara Assifa; Alvin Perdani; Siti Salwa; Indri Ani; Dewi Sartika Panggabean (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the integration of the folklore Legenda Danau Toba in Indonesian language learning as an effort to strengthen students’ cultural identity. The research employed a meta-analysis approach using a systematic literature review method. The data sources were obtained from accredited national journal articles accessed through Google Scholar and published between 2025 and 2026. Data collection techniques included scientific article documentation, article identification, and data classification. The data were analyzed using content analysis through the stages of categorization, synthesis, and interpretation. The findings revealed that the Legenda Danau Toba contains various local wisdom values, such as integrity, environmental awareness, social responsibility, and cultural tolerance. The integration of folklore in Indonesian language learning was found to improve cultural literacy, awareness of local identity, and students’ critical thinking skills. In addition, the implementation of the Culturally Responsive Transformative Teaching (CRTT) approach and creative transformation strategies created more contextual, reflective, and innovative learning experiences. Therefore, local folklore has significant potential as a medium for Indonesian language learning that supports character building and the strengthening of cultural identity among the younger generation.